Increased development of radiographic hip osteoarthritis in individuals with high bone mass: a prospective cohort study - Hartley, April (Arthritis Res Ther, 2021)
BACKGROUND: Individuals with high bone mass (HBM) have a greater odds of prevalent radiographic hip osteoarthritis (OA), reflecting an association with bone-forming OA sub-phenotypes (e.g. osteophytosis, subchondral sclerosis). As the role of bone mineral density (BMD) in hip OA progression is unclear, we aimed to determine if individuals with HBM have increased incidence and/or progression of bone-forming OA sub-phenotypes. METHODS: We analysed an adult cohort with and without HBM (L1 and/or total hip BMD Z-score > + 3.2) with pelvic radiographs collected at baseline and 8-year follow-up. Sub-phenotypes were graded using the OARSI atlas. Superior/inferior acetabular/femoral osteophyte and medial/superior joint space narrowing (JSN) grades were summed and Δosteophyte and ΔJSN derived. Pain and functional limitations were quantified using the WOMAC questionnaire. Associations between HBM status and change in OA sub-phenotypes were determined using multivariable linear/logistic regression, adjusting for age, sex, height, total body fat mass, follow-up time and baseline sub-phenotype grade. Generalised estimating equations accounted for individual-level clustering. RESULTS: Of 136 individuals, 62% had HBM at baseline, 72% were female and mean (SD) age was 59 (10) years. HBM was positively associated with both Δosteophytes and ΔJSN (adjusted mean grade differences between individuals with and without HBM β(osteophyte) = 0.30 [0.01, 0.58], p = 0.019 and β(JSN) = 0.10 [0.01, 0.18], p = 0.019). Incident subchondral sclerosis was rare. HBM individuals had higher WOMAC hip functional limitation scores (β = 8.3 [0.7, 15.98], p = 0.032). CONCLUSIONS: HBM is associated with the worsening of hip osteophytes and JSN over an average of 8 years, as well as increased hip pain and functional limitation.